2000
DOI: 10.1084/jem.191.8.1293
|View full text |Cite
|
Sign up to set email alerts
|

Markedly Different Pathogenicity of Four Immunoglobulin G Isotype-Switch Variants of an Antierythrocyte Autoantibody Is Based on Their Capacity to Interact in Vivo with the Low-Affinity Fcγ Receptor III

Abstract: Using three different Fcγ receptor (FcγR)-deficient mouse strains, we examined the induction of autoimmune hemolytic anemia by each of the four immunoglobulin (Ig)G isotype-switch variants of a 4C8 IgM antierythrocyte autoantibody and its relation to the contributions of the two FcγR, FcγRI, and FcγRIII, operative in the phagocytosis of opsonized particles. We found that the four IgG isotypes of this antibody displayed striking differences in pathogenicity, which were related to their respective capacity to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
154
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(166 citation statements)
references
References 56 publications
12
154
0
Order By: Relevance
“…For example, anti-CD20 mouse IgG1 mAb depletes mouse B cells predominantly through interactions with FcgRIII [29] and a similar finding has been reported in an anaphylaxis model [30]. Additionally, in the model of autoimmune hemolytic anemia in which Ab-mediated erythrophagocytosis is a major pathogenic mechanism, ADCP of mouse IgG1-coated erythrocytes depends on FcgRIII and the IgG1 Ab fails to trigger autoimmune hemolytic anemia in FcgRIII-deficient mice [30][31][32]. These reports and our findings suggest that mouse and rat IgG1 share common effector functions in mice despite the different target cells.…”
mentioning
confidence: 63%
“…For example, anti-CD20 mouse IgG1 mAb depletes mouse B cells predominantly through interactions with FcgRIII [29] and a similar finding has been reported in an anaphylaxis model [30]. Additionally, in the model of autoimmune hemolytic anemia in which Ab-mediated erythrophagocytosis is a major pathogenic mechanism, ADCP of mouse IgG1-coated erythrocytes depends on FcgRIII and the IgG1 Ab fails to trigger autoimmune hemolytic anemia in FcgRIII-deficient mice [30][31][32]. These reports and our findings suggest that mouse and rat IgG1 share common effector functions in mice despite the different target cells.…”
mentioning
confidence: 63%
“…This elevated IgG2a in the PD-L2 -/-mice may contribute to the exacerbated disease observed in these mice. Interestingly, IgG2a has been reported to have the highest binding affinity to macrophages and FccR, while IgG1 has been reported to be a poor interactor [23,24]. The increased Leishmania-specific IgG2a in PD-L2 -/-mice may lead to increased binding of opsonized parasites to FccR and suppress protective immune responses.…”
Section: Pd-l2 -/-But Not Pd-l1 -/-Mice Exhibit Enhanced Levels Of Lmentioning
confidence: 99%
“…It has been shown that some IgG subclasses are more pathogenic than others (39)(40)(41)(42). We therefore examined glomerular deposition of IgG1, IgG2a, IgG2b, and IgG3 (Fig.…”
Section: Proteinuria Kidney Histopathology and Ic Depositionmentioning
confidence: 99%